Agribusiness Business Model Based on the Blue Economy: Synergy Between Agricultural Production and Maritime Logistics - Karjono; Khairullah, Aswin Rafif; Karmanis; Kusumawati, Evyana Diah (Professorline, 2025)
Agribusiness plays a pivotal role in advancing economic growth, food security, and rural welfare, especially in archipelagic nations such as Indonesia where agriculture and maritime activities are geographically intertwined. Yet, fragmented supply chains, limited accessibility, and underdeveloped logistics infrastructure hinder the efficiency and competitiveness of agricultural systems. This study proposes a conceptual business model that integrates agribusiness with maritime logistics under the principles of the Blue Economy. Using a qualitative, desk-based analytical approach, it synthesizes academic literature, policy documents, and development reports to construct a framework aligning agricultural production with ocean-based distribution systems. The model is structured through an adapted Business Model Canvas emphasizing five interlinked components: (1) a value proposition centered on maritime connectivity and sustainability; (2) key integration activities between agricultural processing and sea transport coordination; (3) infrastructure and channel reconfiguration around coastal agrologistics hubs; (4) multi-actor partnerships among farmers, port authorities, and logistics providers; and (5) financial and environmental sustainability mechanisms. The findings highlight that maritime logistics can transform geographic fragmentation into an operational advantage by enabling cost-efficient, low-carbon, and inclusive supply chains. The proposed framework offers a strategic pathway for building resilient agribusiness ecosystems in island nations, supporting food security, regional equity, and sustainable development. While conceptual, the model lays groundwork for future empirical validation and pilot implementation to enhance coordination between agriculture and maritime sectors within Blue Economy-driven growth strategies.